2020
DOI: 10.1111/jomf.12622
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic–Racial Socialization in the Family: A Decade's Advance on Precursors and Outcomes

Abstract: In the current decade, the U.S. population reached historically high levels of ethnic–racial diversity and reelected the nation's first Black–White biracial President. Simultaneously, scholars also documented significant ethnic–racial inequities in education, increased xenophobia, and a racial climate that revealed deep‐seated ethnic–racial tensions. Given this backdrop and acknowledging the significant role that families play in youths' abilities to navigate their social contexts, the current review focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
396
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(417 citation statements)
references
References 148 publications
18
396
2
1
Order By: Relevance
“…Others incorporated key aspects of historical and current phenomena that need intensive examination (e.g., McBride Murry et al, ; Rose, ). Further elaborations of some of this work can be found in the article on ethnic–racial socialization in this issue (Umaña‐Taylor & Hill, 2020).…”
Section: Concluding Comments and Future Directionsmentioning
confidence: 99%
“…Others incorporated key aspects of historical and current phenomena that need intensive examination (e.g., McBride Murry et al, ; Rose, ). Further elaborations of some of this work can be found in the article on ethnic–racial socialization in this issue (Umaña‐Taylor & Hill, 2020).…”
Section: Concluding Comments and Future Directionsmentioning
confidence: 99%
“…Nonetheless, researchers have found that race matters for parenting across the income spectrum in ways perhaps not fully considered by Lareau or Hays (A. Manning, ; Umaña‐Taylor & Hill, ). Dow (, p. 176) found African American middle‐class mothers deployed “experience management” to seek out opportunities for their children, for example, “shuttling sons to activities, such as Little League baseball, basketball or music lessons.” Yet these were not simply efforts to cultivate their unique selves but attempts to expose them to contexts that varied by race, class, and gender so that they would develop the ability to traverse different worlds with aplomb, and in the case of boys in particular, enable them to handle the controlling racialized image of the “thug” (Dow, ; see also Elliott & Aseltine, ; Pugh, ).…”
Section: Family Life Amidst Growing Inequality and Insecuritymentioning
confidence: 99%
“…ERS is commonly defined as the verbal and nonverbal messages and behaviors transmitted from caregivers to youth regarding race and ethnicity. Because racially and ethnically diverse families, particularly those within the African diaspora, contend with chronic racial stressors in multiple contexts, ERS is an essential component of parenting required to prepare youth for encountering and managing racism (Umaña‐Taylor & Hill, 2020). Hughes et al (2006) describe four common ERS messages that families of color, including Black families, report conveying to their children and adolescents.…”
Section: Ethnic–racial Socializationmentioning
confidence: 99%
“…While the lack of consensus regarding preparation for bias and egalitarianism messages and the scarcity of research focused on promotion of mistrust messages for Black adolescents make it difficult to draw strong conclusions about whether these messages benefit Black youth’s psychosocial adjustment, there is growing consensus that the effects of these types of messages are context dependent (Umaña‐Taylor & Hill, 2020). For example, prior research has shown that preparation for bias messages are linked with better psychosocial adjustment in the context of parent–adolescent relationships characterized by communication and trust (Lambert et al, 2015; Tang et al, 2016) and democratic‐involved parenting (Smalls, 2009).…”
Section: Ethnic–racial Socializationmentioning
confidence: 99%